2016
DOI: 10.1007/s10555-016-9637-x
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/AKT/mTOR: role in breast cancer progression, drug resistance, and treatment

Abstract: Anti-cancer cancer-targeted therapies are designed to exploit a particular vulnerability in the tumor, which in most cases results from its dependence on an oncogene and/or loss of a tumor suppressor. Mutations in the phosphoinositide 3-kinase (PI3K)/AKT/mTOR pathway are freqcuently found in breast cancers and associated with cellular transformation, tumorigenesis, cancer progression, and drug resistance. Several drugs targeting PI3K/ATK/mTOR are currently in clinical trials, mainly in combination with endocri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
265
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(287 citation statements)
references
References 76 publications
6
265
0
16
Order By: Relevance
“…All tsRNAs considered are significantly differentially expressed (P < 0.05). (19), PDGF signaling (20,21), sphingosine-1-phosphate (S1P) signaling (22), and mTOR signaling (23)(24)(25)(26). In addition, we observed an inhibition of the tumor suppressor PTEN signaling (27)(28)(29) and ceramide signaling (30).…”
Section: Resultsmentioning
confidence: 76%
“…All tsRNAs considered are significantly differentially expressed (P < 0.05). (19), PDGF signaling (20,21), sphingosine-1-phosphate (S1P) signaling (22), and mTOR signaling (23)(24)(25)(26). In addition, we observed an inhibition of the tumor suppressor PTEN signaling (27)(28)(29) and ceramide signaling (30).…”
Section: Resultsmentioning
confidence: 76%
“…It has also been reported that p63 can activate the Jagged 1/notch pathway [Ma et al, ]; and Jagged 1/notch can regulate the physiological activity of the cells through PI3K/AKT, MAPK, and Wnt pathway [Xiao et al, ]. Besides, according to previous studies, PI3K/AKT plays an important role in tumor cell proliferation and metastasis in many kinds of cancers [Guerrero‐Zotano et al, ; Mayer and Arteaga, ]. Furthermore, miR‐184 exerts its function through different pathways, including AKT pathway to regulate cancer proliferation and invasion [Foley et al, ; Feng and Dong, ].…”
Section: Discussionmentioning
confidence: 98%
“…As PI3K signaling is one of the most hyperactive signaling pathways in breast cancer, targeting this pathway appears to be a promising therapeutic strategy (Cidado and Park, ; Pal and Mandal, ). However, some trials have shown that the use of PI3K inhibitors as a treatment for breast cancer is likely to be limited due to the development of acquired resistance in patients (Guerrero‐Zotano et al, ; Le et al, ). In this study, we found that inhibition of PI3K using LY294002 could stimulate β‐catenin expression in human breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%